2011
DOI: 10.1111/j.1939-1676.2011.0707.x
|View full text |Cite
|
Sign up to set email alerts
|

Holter Monitoring in Clinically Healthy Cavalier King Charles Spaniels, Wire‐Haired Dachshunds, and Cairn Terriers

Abstract: Background: Few reported studies describe normal values from 24-hour ECG (Holter) recordings of small breed dogs. Objectives: To investigate influence of breed, age, sex, body weight, degree of recording artifact, and mitral valve prolapse (MVP) on Holter recordings of 3 breeds of small dogs that have differing predispositions for myxomatous mitral valve disease. The study also assessed if heart rate (HR) at clinical examination (HRex) was associated with HR during Holter monitoring and evaluated the reproduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 31 publications
(48 reference statements)
5
53
1
1
Order By: Relevance
“…In addition, only group and breed independently affected the progression of HR and VVTI over time. A related finding has already been shown by Rasmussen et al17 who showed that CKCS have lower HRV. In addition, a recent cross sectional study evaluating urinary catecholamines in healthy dogs showed breed differences in blood pressure, HR, and also in both epinephrine to creatinine ratio and norepinephrine to creatinine ratio,18 implying breed variation in autonomic tone.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, only group and breed independently affected the progression of HR and VVTI over time. A related finding has already been shown by Rasmussen et al17 who showed that CKCS have lower HRV. In addition, a recent cross sectional study evaluating urinary catecholamines in healthy dogs showed breed differences in blood pressure, HR, and also in both epinephrine to creatinine ratio and norepinephrine to creatinine ratio,18 implying breed variation in autonomic tone.…”
Section: Discussionsupporting
confidence: 77%
“…Results have shown substantial breed differences in plasma concentrations of the natriuretic peptides pro‐ANP 31‐67 and NT‐proBNP,11 prompting cautiousness when using them as biomarkers for heart disease. When investigating a subpopulation of the dogs, we also found breed differences in blood pressure and heart rate in consistency with other studies,12, 13, 14 and in urinary epinephrine and norepinephrine concentrations 15…”
supporting
confidence: 91%
“…The breed variation could partly be explained by genetic background, as illustrated by the closely related breeds, German and Belgian Shepherds, having very similar distributions of both proANP 31‐67 and NT‐proBNP. Previous studies have shown breed differences in cardiovascular variables such as blood pressure, heart rate, and catecholamine concentrations 41, 42, 43. Tachycardia has been associated with increased plasma concentrations of ANP in people as well as in dogs and has been suggested to depend primarily on increased atrial pressure 44, 45.…”
Section: Discussionmentioning
confidence: 99%